009 Incidental findings in CTCA. (5th May 2016) - Morrison, Julie; Philip, Liz
Abstract : Background: CT coronary angiograms have been performed at the Golden Jubilee National Hospital since 2004 and with the installation of the GE 750 HD scanner in 2010, a cardiologist led service for CTCA was set up. To comply with BSCI guidelines, the non-contrast calcium score was reconstructed to provide a larger field of view for radiologists to report non-cardiac elements of the scans. After discussion with the lead radiologist, a decision was made to split both non-contrast and contrast series and retrospectively reconstruct them into larger display field of view to allow radiologists to report the non-cardiac elements from both series. This audit was carried out to investigate the number of incidental radiological findings reported on CTCA scan and their clinical significance. Method: Data was collected retrospectively from the non-cardiac section of reports generated from CTCA scans performed between February–July 2015 inclusive. Any incidental findings were noted and recorded. Results: 407 CTCA scans were performed between February–July 2015, within this group of 173 patient scans, 42%, were reported with incidental findings. Most significantly within this cohort, 4 patients (2%) required immediate treatment for pulmonary embolus. 2 patients (1%) required urgent referral for suspicious chest mass. 2 patients (1%) required 3–4 month CT follow up for chest mass. Conclusion: A large proportion of patients scanned were reported with incidental findings in the chest/upper abdominal area. The majority were benign, requiring no urgent follow up. However a small percentage was reported to have significant clinical findings which required urgent or immediate referral/treatment. Therefore the audit has demonstrated the importance of reconstructing both pre and post contrast large field of view images in order to visualise pathology which may be hard to distinguish in the non contrast phase. The audit has also highlighted the importance of a multi-disciplinary approach when reporting both cardiac and non-cardiac elements of the CTCA scan.